Lepirudin treatment in a boy with suspected HIT II after surgery because of tetralogy of Fallot - Hanke, C. A.; Barth, K.; Nakamura, L.; Budde, U.; Arnold, R.; Zieger, B.; Stiller, B. (Hämostaseologie, 2009)
Heparin-induced thrombocytopenia (HIT II) in childhood is rare. Suspected HIT II requires immediate diagnostic and therapeutic measures in order to avoid potentially life threatening complications. Heparin must be stopped immediately.We report on a 6-year old boy who required cardiac surgery due to tetralogy of Fallot. To our knowledge he had been exposed to heparin for the first time during cardiac catheterization on the day before surgery. Preoperatively, platelet count was normal. Postoperatively (3 days after heparin exposure), he developed pulmonary and renal failure and required inotropic cardiac support and dia -lysis. He also developed progressive (severe) thrombocytopenia under heparin therapy on day 2–3 postoperatively. The dialysis filter required daily exchanges due to clotting despite increasing heparin doses. The first ELISA for HIT on postop day 4 was negative. 3 days later a repeated test was positive. Von Wille-brand factor antigen and D-dimers were markedly increased. The patient was immediately switched to lepirudin and subsequently stabilized slowly. No major systemic thrombosis occurred. After lepirudin treatment for 6 weeks the patient was fully recovered and HIT II-testing was negative again. Conclusion: In children with progressive thrombocytopenia in the setting of heparin exposure and signs of major or micro thrombosis HIT II must be ruled out. Even if a first early test turns out negative repeated testing should be performed. Lepirudin anticoagulation is effective and should be monitored correctly. Platelet transfusion should be avoided in HIT II.
Keywords: HIT; child; lepirudin; cardiac surgery; renal failure; thrombocytopenia